Surface snow bromide and nitrate at Eureka, Canada, in early spring and implications for polar boundary layer chemistry - X. Yang; K. Strong; A. S. Criscitiello; M. Santos-Garcia; K. Bognar; X. Zhao; P. Fogal; K. A. Walker; S. M. Morris; P. Effertz (Atmospheric Chemistry and Physics, 2024)
This study explores the role of snowpack in polar boundary layer chemistry, especially as a direct source of reactive bromine ( BrO x = BrO + Br ) and nitrogen ( NO x = NO + NO 2 ) in the Arctic springtime. Surface snow samples were collected daily from a Canadian high Arctic location at Eureka, Nunavut (80° N, 86° W) from the end of February to the end of March in 2018 and 2019. The snow was sampled at several sites representing distinct environments: sea ice, inland close to sea level, and a hilltop ∼ 600 m above sea level ( a . s . l . <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="31776a712c7ed4315f8e2af6609516eb"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-24-5863-2024-ie00001.svg" width="25pt" height="10pt" src="acp-24-5863-2024-ie00001.png"/></svg:svg> ). At the inland sites, surface snow salinity has a double-peak distribution with the first and lowest peak at 0.001–0.002 practical salinity unit ( psu ), which corresponds to the precipitation effect, and the second peak at 0.01–0.04 psu , which is likely related to the salt accumulation effect (due to loss of water vapour by sublimation). Snow salinity on sea ice has a triple-peak distribution; its first and second peaks overlap with the inland peaks, and the third peak at 0.2–0.4 psu is likely due to the sea water effect (a result of upward migration of brine). At all sites, snow sodium and chloride concentrations increase by almost 10-fold from the top 0.2 to ∼ 1.5 cm . Surface snow bromide at sea level is significantly enriched, indicating a net sink of atmospheric bromine. Moreover, surface snow bromide at sea level has an increasing trend over the measurement period, with mean slopes of 0.024 µM d −1 in the 0–0.2 cm layer and 0.016 µM d −1 in the 0.2–0.5 cm layer. Surface snow nitrate at sea level also shows a significant increasing trend, with mean slopes of 0.27, 0.20, and 0.07 µM d −1 in the top 0.2, 0.2–0.5, and 0.5–1.5 cm ...